Comparative evaluation of antigen detection ELISA and reverse transcriptase PCR in acute stage of Japanese encephalitis prevalent in endemic areas of North-Eastern part of Uttar Pradesh, India - Verma, Rajesh Kumar; Singh, Dharmendra Prasad; Yadav, Ramakant; Rawat, Ramakant (International Journal of Research in Medical Sciences, 2017)
Background: Objective of current study was to compare and evaluate different diagnostic tests to establish a reliable and less time consuming diagnostic test for prompt diagnosis of acute Japanese encephalitis cases mainly amongst children and young adults from North-Eastern part of Uttar Pradesh. Methods: A total of 100 subjects, including 50 suspected cases and 50 diseased controls were investigated to establish the diagnosis of JE in acute encephalitis patients. All CSF samples were subjected to MAC-ELISA, virus cultivation and RT-PCR. Results: Out of 50 cases, 6 showed negative results by all the three tests. 50% (22 out of 44), 47.5% (21 out of 44), and 66% (23 out of 44) were found positive by MAC-ELISA, Virus cultivation and RT-PCR respectively. The rate of detection by Virus cultivation and RT-PCR was higher in case of MAC-ELISA negative cases (57.1% and 78.5%) than that of MAC-ELISA positive cases (22.7% and 27.2%) respectively. Mean age of the patients was 12.5 years, which ranged from 1-24 years with male to female ratio of 3:1. Conclusions: The RT-PCR was found most reliable, sensitive and specific method amongst the three chosen methods for detection of JEV in suspected encephalitis patients.